PEMBUKTIAN TERBALIK KASUS TINDAK PIDANA KORUPSI DALAM PERSPEKTIF HAK ASASI MANUSIA - Hasuri Hasuri; Mia Mukaromah (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2020)
Corruption is considered a great crime and requires special handling. In handling corruption, special handling is needed by using the proof reversed or reversal of the burden of proof but in a balanced manner. The purpose of this study is to explain the reverse evidence of corruption from a human rights perspective. This research uses the empirical normative legal research method, namely the combination of normative legal provisions (laws) with practical elements (legal events in society/social elements). The study results state that the theory of reverse proof of corruption cases based on a human rights perspective does not violate the principles and respect for the rights of the defendants in the general principles of criminal law.